The Advice Genre (1400-1599). Genre and Text Type Conventions - Barrera, Ivalla (Studia Anglica Posnaniensia, 2010)
The aim of this paper is to characterize the advice text as a genre in the late medieval and early modern English periods. This genre is very popular during this time and is usually found within medical remedy books. For this reason, it has been generally studied within the scope of medieval recipes in historical discourse analysis. In this paper my intention is to show the independent status of the advice text as a genre. A first step for this lies in the characterization of the linguistic features pertaining to the sections that compound this genre and its comparison with the recipe genre. The corpus for this study has been collected from several sources, both edited and unedited. The description of the text type features will be illustrated with examples taken from this corpus. As I show in the conclusion, the advice text is an independent genre with a clear communicative purpose and addressed to an intended audience.